2012
DOI: 10.1007/s12010-011-9493-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Anaerobic/Aerobic Treatment of Dye-Containing Wastewaters: Colour and COD Removals, and Ecotoxicity Tests

Abstract: Colour and COD removals of the azo dyes Congo Red (CR) and Reactive Black 5 (RB5) were individually evaluated in a sequential anaerobic/aerobic treatment system. Additionally, dye toxicity was assessed by using acute ecotoxicity tests with Daphnia magna as the indicator-organism. The anaerobic reactor was operated at approximately 27 °C and with hydraulic retention times of 12 and 24 h. The aerobic reactor was operated in batch mode with a total cycle of 24 h. During anaerobic step, high colour removals were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 38 publications
(51 reference statements)
0
10
0
2
Order By: Relevance
“…Azo compounds with a hydroxyl or amino groups are more likely to be degraded than those with methyl, methoxy, sulpho, or nitro groups (Supaka et al 2004). It has been reported that dyes with simple structures and low molecular weights exhibit higher rates of decolourization than those with high molecular weight and high substitutions (Solis et al 2012;Da Silva et al 2012 The lesser decolourization of RB5 was attributed to its high molecular weight and highly substituted chemical structure as compared to that of CR (see Fig. 1).…”
Section: Dye Structurementioning
confidence: 94%
See 4 more Smart Citations
“…Azo compounds with a hydroxyl or amino groups are more likely to be degraded than those with methyl, methoxy, sulpho, or nitro groups (Supaka et al 2004). It has been reported that dyes with simple structures and low molecular weights exhibit higher rates of decolourization than those with high molecular weight and high substitutions (Solis et al 2012;Da Silva et al 2012 The lesser decolourization of RB5 was attributed to its high molecular weight and highly substituted chemical structure as compared to that of CR (see Fig. 1).…”
Section: Dye Structurementioning
confidence: 94%
“…Thus, the mixed microbial consortia can carry out tasks better than or equivalent to that of an individual pure culture without any precautions to prevent contamination. Different reactor configurations, such as the widely used upflow anaerobic sludge blanket (UASB), expanded granular sludge bed (EGSB), anaerobic/aerobic sequential batch reactor (SBR), activated sludge process (ASP), have been reported for efficient dye decolourization using mixed microbial consortia (Dos Santos et al 2007;Karatas et al 2010;Yasar et al 2012;Da Silva et al 2012). The biodegradation of azo dyes occurs in a two-step process (Rai et al 2005;Vanderzee et al 2001).…”
Section: Decolourization Of Dyes: Pure Versus Mixed Microbial Culturesmentioning
confidence: 99%
See 3 more Smart Citations